Theoretical investigation of turning ability of machine and tractor aggregate on basis of ploughing and intertilling wheeled tractor - Bulgakov, V.; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Ivanovs, S.; Adamchuk, V.; Nadykto, V.; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович (My University, 2016)
The turning ability of tractors, which is estimated as a minimal value of the turning radius, is one of the most important characteristics of their efficient performance. As a result of theoretical simulation an equivalent scheme has been built for a complex of a wheeled tractor and a trailed agricultural machine, a system of equations has been built for uniform turning of the aggregate, and analytical expressions were defined for two unknown parameters: the curvature of the path of motion and the coordinates for displacement of the turning centre. As a result of numerical simulation graphic dependencies have been built: of the turning radius of the aggregate and the longitudinal coordinate on the turning angle of the steering wheels of the tractor; of the turning angles of the front and rear wheels of the tractor on the turning radius of its steering wheels; and of the turning angle of the machine and tractor aggregate on the turning angle of the steering wheels. The results of the theoretical research made it possible to estimate with high precision the turning ability of the machine and tractor aggregate depending on the design and kinematic parameters of the tractor and the trailed agricultural machine.
Keywords: wheeled tractor; machine and tractor aggregate; turning angle